2011
DOI: 10.1111/j.1365-277x.2011.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Body mass, frequency of eating and breakfast consumption in 9–13‐year‐olds

Abstract: Older boys were the least likely to eat regularly and the least likely to consume breakfast. Promoting the importance of regular eating, particularly breakfast consumption to these boys, may be essential to ensure healthier, long-term eating patterns. Furthermore, the lower breakfast intakes in 11-13-year-olds and higher BMI Z-scores of those who did not eat breakfast regularly should be monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…One possible explanation for this relationship may be dissatisfaction with body image and the intention to lose weight due to media pressure and desire for thinness [32,41]. On the other hand, some authors [37,42], found no gender difference in breakfast skipping prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this relationship may be dissatisfaction with body image and the intention to lose weight due to media pressure and desire for thinness [32,41]. On the other hand, some authors [37,42], found no gender difference in breakfast skipping prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity in adolescence predisposes a young person to heart disease, type 2 diabetes, stroke, several types of cancer and osteoarthritis (2, [12][13][14][15][16]. It has also been suggested that obesity in adolescence may adversely affect academic performance (12)(13)(14)(16)(17)(18)(19)(20)(21). It is important to remember that obesity and nutritional deficiencies are not mutually exclusive, there may be a double burden for many of both obesity and nutrient deficiencies (such as iron deficiency and zinc deficiency) (11,22).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of breakfast skippers in this study was not much different from study in UK to 4,326 school children aged 10-16 years that showed that as many as 25 % of children often skip breakfast, and 7% did not eat breakfast (15), but lower when compared with a UK study on 264 children aged 10-13 years-old which showed that as many as 55% of children who were not breakfast everyday (16) and from a study of 426 children aged 10-14 years-old in Hong Kong, which showed that 30.5% of children skipped breakfast at least once in a week, and 33.7% of them more often, so there was only 35% of children who ate breakfast everyday (17). Research in Italy at the elementary and junior high school, stated that there were 48% of children who were breakfast skippers (18).…”
Section: Breakfast Habits Of Elementary School Childrenmentioning
confidence: 48%